answersLogoWhite

0


Best Answer

-6z + 16 = 52 subtract 16 from each side

-6z = 36 divide by -6

z = -6

User Avatar

Wiki User

โˆ™ 2012-10-25 01:03:57
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.72
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
335 Reviews

Add your answer:

Earn +20 pts
Q: What is the solve two step equation of -6z plus 16 equals 52?
Write your answer...
Submit
Related questions

How do you substitute y equals 4 into the equation x plus y equals 5?

y=4 x+y=5 so it wud be:::::: x+4=5 solve it from there by doing 1 step equation :)


What is the first step in solving the equation 7q plus 9 equals 3?

the first step in solving the equation is to subtract the nine from the three. you will get negative 6.


What step would you take to solve the equation x plus 11 equals 37?

X + 11 = 37. subtract 11 from both sides; X = 37 - 11 = 26.


What is a two step equation that equals 2?

An example of a two step equation that equals 2 is 4 + 2x = 2. In this equation, x = -1.


What is the first step in solving the equation 7d plus 1 equals 8 for d?

Subtract 1 form both sides of the equation


What is a Multi step equation that solves for X equals 6?

You do not need any steps to solve X = 6! The solution is already given!!!X equals 6.


How do you do two step equations?

AN two step equation is an equation that requires two steps to solve


What is the first step in solving this equation by completing the square?

The first step would be to find the equation that you are trying to solve!


What is the solution to this equation negative 2x plus 14 equals 0?

2x + 14 = 0Subtract 14 from each side of the equation: 2x = -14Divide both sides of the equation by 2: x = -7You can also obtain solutions to equations by visting wolframalpha.com. Enter solve 2x+14=0, for example. You can click on the 'step-by-step' button to see how the equation was solved.


What multi-step equation equals 12?

2x3x2


What is a 4 step equation that equals 8?

Full


What is a multi step equation that equals 13?

13


What is 4.6b plus 26.8 equals 50.72?

It's a first-degree equation in 'b' . To solve the equation in two steps: 1). Subtract 26.8 from each side of the equation. 2). Divide each side of the equation by 4.6 . 3). If your solution is not [ b = 5.2 ], go back to Step-1 and repeat until you do it correctly.


How do you do the math narrative?

whatever the equation is write the equation in words then solve each step in a sentence.


What is x plus 8 equals 11?

x=3 For the equation x + 8 = 11, only one step is required to solve for x Subtract 8 from both sides of the equation to get the x term by itself. 11-8=3, so x=3


How do you solve the math problem What is my number?

use one step equation.


How can you decide which operations to use to solve a two step equation?

yh


What is a 2 step equation that equals 10?

2 15=


What is a 2 step equation that equals 9?

it is 3x3 not that hard


What is a 2 step equation that equals 13?

3x4+1


How do you solve 5p 15 equals 15 5p?

-- Add 5p to each side of the equation. -- Add 15 to each side of the equation. -- Look at the equation and find the one last step that will give you " p = a number ", which is the solution.


What is the first step in solving the equation t mines 17 equals 48?

t - 17 = 48 The first step is to move the -17 to the right side of the equation and end up with: t = 48 + 17. (When you switch sides, the sign changes) To solve the equation: t = 65


What is one step equation?

an equation that only requires one operation done to solve it or so i believe


How do you solve quadratic functions step by step?

There are different methods of using quadratic functions depending on the equation.


How can you solve -2x equals -4x plus 24 step by step?

-2x = -4x + 24 -2x + 4x = 24 2x = 24 x = 24/2 x = 12